Subtle Cerebellar Features in Relatives of Essential Tremor Cases - Hale, Evan A.; Hickman, Ruby; Dowd, Hollie; Varathan, Deepti; Liu, Gina; Louis, Elan D. (Frontiers in Neurology, 2020)
Background: Essential tremor (ET) cases often exhibit a range of mild cerebellar signs. Their unaffected relatives have been shown in prior studies to exhibit subtle (i.e., pre-clinical) disease features. Objective: To quantify subtle cerebellar signs in unaffected first-degree relatives of ET cases stratified based on their tremor severity. Methods: 269 first-degree relatives of ET cases, none of whom reported tremor or a diagnosis of ET, or were diagnosed with ET based on detailed neurological examination, were stratified based on total tremor score (TTS) into two groups (lower TTS vs. higher TTS) and quartiles. Changes in gait, balance and intention tremor were quantified on neurological examination. Results: Higher TTS performed worse on the tandem stance task (p = 0.011). When stratified into TTS quartiles, higher quartile was associated with worse performance in tandem stance (p = 0.011) and stance with feet together (p = 0.028). Similarly, intention tremor in the arms (p = 0.0002) and legs (p = 0.047) were higher in the groups with more tremor. Discussion: The links between ET and the cerebellum are multiple. These data provide intriguing evidence that subtle cerebellar signs (i.e., changes in balance and intention tremor) are more prevalent among first-degree relatives of ET cases with more tremor (i.e., those who may be themselves on the pathway to developing ET). These data contribute to a better characterization of what may be an early sub-clinical stage of the disease.